Evaluation of Community Scholarship Training Program in Fulfillment of 35GW Coal Based Power Plant Operator - ., Ineza; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract. Human Resources Development Center of Electricity, Renewable Energy and Energy Conservation under the Human Resources Development Agency of Energy and Mineral Resources the Ministry of Energy and Mineral Resources has an obligation to implement human resource development in the Electricity, Renewable Energy and Energy Conservation sectors. One of the programs being launched by the government to support the availability of electrical energy in Indonesia is the 35,000 MW electricity program. The power plant development program needs to be followed up with the preparation of competent technical personnel. This study aims to provide an evaluation of the implementation of community-based human resource development policies in the fulfillment of 35000 MW operators program operators conducted by the Center for Human Resource Development KEBTKE through education and training assistance policy for the community as stipulated in Minister of Energy and Mineral Resources Republic of Indonesia Regulation 36, 2015 and its implementation. Indonesia's multi-stakeholder governance system proved to be a challenge in the formulation stage of policy and policy implementation. Some important findings in this program are the workforce preparation program through the community-based training is also the main duties and functions of the ministry of labor so that the need for special coordination related to the preparation of manpower by the Ministry of Energy and Mineral Resources. In addition, the program only sets short-term policy objectives to be implemented within a small scope: preparing workers through community empowerment programs around the plant, and not facilitating the funding on the job training and certification activities, requiring strong cooperation with the company. Lack of coordination between stakeholders has become one of the main factors of the continuity of this program. Furthermore, the final project provides recommendation based on the results of the obtained evaluation. The method used is literature study, collecting data through survey, filling questionnaire and interview.Â Keywords: Training Evaluation, Program Evaluation, Community Empowerment, Coordination, 35000 MW.